2008
DOI: 10.1055/s-2008-1045002
|View full text |Cite
|
Sign up to set email alerts
|

Carbonband-Implantate im Tierexperiment. Licht- und transmissionselektronenmikroskopische Untersuchungen zur Biokompatibilität

Abstract: Part of the patella ligament was resected in rabbits and replaced by carbon fibre implants. After 1, 2, 3, 6 weeks, 3 and 12 months carbon implants with surrounding tissues as well as iliac lymph nodes were removed and examined by light- and transmission electron microscopy. Of special interest were the questions whether the carbon fibre implant, will be removed by phagocytosis and substituted by a new ligament or a adequate repair tissue? Our light- and transmission electron microscopic studies give no indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Biocompatibility of CFs has been the subject of numerous researches. Some of investigators concluded that CFs induce the growth of new tissue [2], however, there were also announcements questioning biocompatibility of CFs [35]. The different opinions regarding biocompatibility of CFs may be explained by the use of different types of CFs of different physical, structural and chemical properties, resulting from many technological parameters [3, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility of CFs has been the subject of numerous researches. Some of investigators concluded that CFs induce the growth of new tissue [2], however, there were also announcements questioning biocompatibility of CFs [35]. The different opinions regarding biocompatibility of CFs may be explained by the use of different types of CFs of different physical, structural and chemical properties, resulting from many technological parameters [3, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, strategic incorporation of the carbon fibers into a biodegradable scaffold can ensure the continued loadbearing function of the targeted tissue. In addition, previous invitro and in-vivo studies on the other carbon fibers have yielded controversial results showing that the carbon fibers induced the growth of new tissue (11,22) and other studies yielded opposite results (23,24). Bone, ligaments, and tendon application have been previously the main focus of biocompatibility studies for carbon fibers.…”
Section: Discussionmentioning
confidence: 99%